2021
DOI: 10.1177/14644207211053963
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic characterization of fiber elastomer metal laminate composites and effect of positioning of fiber reinforced elastomer

Abstract: The present study aims at investigating the ballistic impact response of jute, natural rubber and aluminium based tri-layer composites with two different configurations, namely Aluminium-Jute-Rubber-Jute and Jute-Rubber-Jute-Aluminium. The proposed composites were fabricated using the compression moulding technique and subjected to ballistic impact testing at impact velocities of 75 m/s, 105 m/s, 154 m/s and 183 m/s. The energy absorption and damage mitigation characteristics of the proposed fibre metal elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Layers in such constructions can be made of various materials [2][3][4] that are selected and arranged in a proper way to prevent perforation of the armor [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Layers in such constructions can be made of various materials [2][3][4] that are selected and arranged in a proper way to prevent perforation of the armor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the search for optimal solutions is directed towards composite and multilayered structures. Layers in such constructions can be made of various materials [ 2 , 3 , 4 ] that are selected and arranged in a proper way to prevent perforation of the armor [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Several studies have investigated the energy absorption characteristics of rubber-based composites. Mahesh et al 11 evaluated the impact behavior of rubber-based fiber metal laminates and reported improved energy absorption compared due to inclusion of rubber. Furthermore, research on natural fiber composites, including kenaf, has demonstrated their potential for energy absorption applications.…”
Section: Introductionmentioning
confidence: 99%
“…12,21 Elastomer materials have been employed in shock absorbent sheets, dampers, and other technical applications. [22][23][24][25] Making use of elastomer components in composites is an innovative technique to enhance the impact behaviour and mitigate the failure. Experiments by Sarlin et al 26 studied the impact behaviour of hybrid composite laminate fabricated using elastomer, GFRRP and steel as the constituents as a function of impact energy and rubber thickness.…”
Section: Introductionmentioning
confidence: 99%